Spray deposition and uniformity assessment of unmanned aerial application systems (UAAS) at varying operational parameters - Byers, Coleman; Virk, Simerjeet; Rains, Glen; Li, Steve (Frontiers in Agronomy, 2024)
The use of Unmanned Aerial Application Systems (UAAS) has increased rapidly in agriculture in recent years. Information regarding their spray performance, as influenced by operational parameters, is important to understand for their effective utilization. A study was conducted to assess the spray characteristics of two commercial UAAS platforms (TTA M4E and DJI Agras T30) using three different nozzle types, flight speeds, and application heights. Spray deposition was recorded across the swath to assess and compare spray behavior under these selected varying operational parameters. In-swath deposition uniformity was evaluated using the coefficient of variation (CV) for different theoretical effective swaths computed from single-pass spray patterns. The results indicated a highly variable spray deposition with the majority of coverage concentrated directly below the UAAS flight path. Coarser droplets produced by the AIXR (Air-Induction Extended Range) and TTI (Turbo Teejet Induction) nozzles exhibited greater coverage directly under the UAAS while finer droplets from the XR (Extended Range) nozzle showed improved uniformity across wider swaths. Coverage decreased with an increase in flight speed for both platforms. Application height had no effect on spray coverage for the TTA M4E, but coverage increased with height for the DJI Agras T30 within the tested range. Both increased flight speed (5.0 and 6.7 m s-1 for the TTA M4E and DJI Agras T30, respectively) and height (3.0 m for both the TTA M4E and DJI Agras T30) showed increased uniformity. Among the tested parameters, only a few exhibited an acceptable variability (CV≤25%) within the range of theoretical effective swaths. The TTA M4E had a CV<25% for the flight speeds of 3.4 and 5.0 m s-1, and a height of 3.0 m at an effective swath of 2.0 m. In contrast, the 2.3 and 3.0 m heights, XR and TTI nozzles, and 4.5 and 6.7 m s-1 speeds exhibited acceptable variability for the DJI Agras T30 for an effective swath of 4.0 m. For both UAAS, none of the tested parameters had an acceptable CV (≤25%) at the widest swath (4.0 and 9.0 m for the TTA M4E and DJI Agras T30, respectively) recommended by the manufacturer.